O poder público inadimplente: uma busca por mecanismos para garantir o cumprimento de obrigações do poder concedente em contratos de concessão de serviço público - Tourinho, Anna Carolina Morizot (2018)
Currently, in Brazil, there is a movement to change the relationship of the public and private sector from a supremacy of the Government status to a more consensual and collaborative relationship. That is because this extraordinary power system used in the concession agreement is proving to be inefficient, costlier, and is being used to support authoritarian practices from the Government. In that context, is urgent to reconsider this superior position that the Government exercise in concession agreements. This paper searched in the national and international doctrine the reasons why it was understood to be important for the Government to have these special powers in such contracts. It was searched in judicial precedents what is the most common forms of the Government´s default. It was analyzed several preventive and reactive mechanisms to avoid the default to happen, to respond to the non-compliance compelling the Government to act as established in the contract, and to compensate the private partner in case it is impossible to meet the agreement. It was understood that the best way to ensure the public interest is to reduce the extraordinary powers from the Government, ensuring legal certainty and reducing the costs to the Government as a partner